Quantifying capacity for burn care in South Africa - N.L. Allorto; S. Wall; D.L. Clarke (Elsevier, 2018)
The Lancet Commission on Global surgery has highlighted the fact that the vast majority of surgical care is delivered and consumed in high income countries (HIC's) yet about two thirds of the burden of surgical disease is in low and middle income countries (LMIC) where resources are grossly inadequate. In light of this we set out to audit the current resources available to treat burns in South Africa to quantify the extent of the resource deficit which needs to be addressed if we wish to close the gap in outcomes between South Africa and the developed world. Data was collected for seven out of the nine provinces. There are a total of 17 burn units with 511 beds and 8140 admissions per year across the country.Although there are some deficits in the infrastructure and staffing available to treat burn injuries in South Africa, for example access to isolation, after hours cover, dedicated temperature controlled theatres, this is difficult to alter without government buy in and the current fiscal environment. It would appear that process of care (what you do with what you have) is lacking and needs more development for example establishment of a national registry to facilitate data collection and audit, as well as the introduction of outreach programs, protocols and improving theatre efficiency. Keywords: Quality improvement, Management capacity